Buildings at 14 Franciszkańska Street and 24 Fosa Staromiejska Street in Toruń in the light of architectural research and source queries - Kucharzewska, Joanna (Budynki przy ul. Franciszkańskiej 14 i Fosa Staromiejska 24 w Toruniu w świetle badań architektonicznych i kwerend źródłowych, 2022)
The article presents the results of architectural research carried out at the basement level at 14 Franciszkańska and 24 Fosa Staromiejska Streets in Toruń. The aforementioned research was supplemented with source studies concerning both cellars and above-ground parts. The aim of the architectural research was to determine stages of construction on the plots in question from the Middle Ages to the beginning of the 20th century. An important issue was to identify the content of the oldest historic substance from the medieval period and the moment of functional and spatial integration of the opposite plots. The plot is located in the northern part of the Old Town of Toruń, within a triangular block of buildings, the outline of which was determined by the course of the north-eastern section of the city walls. Currently, on two opposite plots there is a tenement house, which received its final shape in the early 20th century. During the research, it was found that the oldest, Gothic fragments are present in the southern part (on the side of Franciszkańska Street). In the second Gothic stage, the northern part (from the side of Fosa Staromiejska Street) was given a basement and the stone foundations of the earlier building were used to create it. In the modern period, the two parts, which had been two independent units until then, were connected by a side outbuilding. In the 18th century, on the plot facing Franciszkańska Street, there was a two-story, brick granary. From the side of Fosa Staromiejska Street, there was a timber frame coach house. Both buildings burnt down at the beginning of the 19th century. In the mid-19th century, a large, fivestorey granary covering both plots was erected. The granary was founded on medieval and modern cellars. The ultimate change of buildings took place in 1906, when, after the demolition of the granary, two tenement houses were built with a common central route containing a staircase and an inner courtyard. Architectural research together with the source material was an effective tool for reconstructing individual stages of construction and expanding our knowledge about the forms of development of the walled part of the Old Town in Toruń.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2022, nr 4 (72), s. 91-102
Keywords: architektura; architectural research; Toruń; 14 Franciszkańska Street; 24 Fosa Staromiejska Street; badania architektoniczne; ul. Franciszkańska 14; Fosa Staromiejska 24